2016
DOI: 10.1186/s12882-016-0281-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of the Essential Amino Acids and Keto-Analogues on the CKD progression rate in real practice in Russia - city nephrology registry data for outpatient clinic

Abstract: BackgroundRenal replacement therapy (RRT) is growing by 10 % per year in Russia, but pre-dialysis care which can retard CKD progression and delay the start of RRT remains limited. We evaluate the effect of Essential Amino Acids and Keto-analogues (EAA/KA) on CKD progression.MethodsThe effect of low protein diet (LPD), supplemented by EAA/KA, on GFR slope changes between first and second treatment period (five sequential visits per period) in 96 patients withs CKD Stage 3B-5 was compared to GFR slope changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
(22 reference statements)
0
5
0
Order By: Relevance
“…A subsequent study by Zemchenkov et al of 96 CKD patients with stage 3b-5 confirmed that an LPD supplemented with essential amino acids and KAs induced a slowdown in the progression of CKD, particularly in female elderly patients and in those with low levels of plasma phosphorus [ 132 ].…”
Section: Nutritional Therapymentioning
confidence: 97%
“…A subsequent study by Zemchenkov et al of 96 CKD patients with stage 3b-5 confirmed that an LPD supplemented with essential amino acids and KAs induced a slowdown in the progression of CKD, particularly in female elderly patients and in those with low levels of plasma phosphorus [ 132 ].…”
Section: Nutritional Therapymentioning
confidence: 97%
“…In the ‘80s and ‘90s, Giovannetti and Locatelli began the Integrated Dialysis Dietary Program (IDDP) in patients with GFR < 3 ml/min/1.73 m 2 , consisting of a weekly hemodialysis session integrated with a very low protein diet equal to 0.3–0.4 g/kg/day (VLPD) supplemented by essential amino acids and their ketoanalogues [ 101 , 102 ]. Even then, the perception that DNT was an important therapeutic tool for delaying the start of dialysis was established [ 103 105 ]. Numerous other reports demonstrate that duration and/or frequency of dialysis produces pro-inflammatory and pro-oxidative cytokine stress which leads a reduction in RRF [ 106 ].…”
Section: In Selected Patients Proper Dietetic-nutritional Therapy Camentioning
confidence: 99%
“…Recently, a well-defined, randomized, controlled trial demonstrated that vegetarian VLPD supplemented with ketoacid analogs delayed dialysis initiation among patients with advanced CKD with GFR less than 20 to 30 mL/min/1.73 m 2 by ameliorating metabolic disturbances [22]. Finally, recent meta-analyses and real clinical practice in nephrology registry supported that VLPD or LPD, supplemented with ketoacid analogs, significantly prevented the deterioration of GFR [10,23,24]. Related clinical trials were investigated among patients with very late stages of CKD or CKD stage V, who wished to defer dialysis treatment.…”
Section: Discussionmentioning
confidence: 99%